Implikasi Self-care untuk Psychological Well-Being pada Professional Helper - Syifa Fauza; Ribut Purwaningrum; Adi Dewantoro (Jurnal Psikoedukasi dan Konseling, 2022)
This study aimed to (1) describe the process of selecting articles the literature on the implication of self-care on professional helpers’ psychological well-being, (2) describe the role of self-care in professional helpers’ psychological well-being, (3) depict the self-care for professional helpers’ psychological well-being, and (4) describe the form of self-care for professional helpers’ psychological well-being. This approach extends the current knowledge and provides a basis for the policy- making process and practice. The data were collected from twenty-five articles in electronic databases. The data were documented following Siddaway, Wood, and Hedges’ (2018) proposed stages. The data were analyzed using the content analysis technique. Relevant articles were analyzed in-depth to extract necessary information. This study found the selection process for articles in this study was carried out through selecting duplicate articles, selecting titles and/or abstracts, and selecting the entire contents of the articles. Articles agreed that self-care might affect professional helpers’ psychological well-being. Articles view self-care for professional helpers’ psychological well-being as an activity to care for themselves and their profession. Articles divided self-care for professional helpers into two categories: personal self-care and professional self-care. Although studies on self-care for professional helpers’ psychological well-being have been conducted, further understanding of self-care for professional helpers is still necessary. Thus, professional helper associations are recommended to conduct training and monitor self-care implementation. Future studies are recommended to obtain field evidence of self-care to maintain psychological well-being.